Reluctant Collaborators: China-Russia Co-Publications over the Past Decade - John P. Haupt; Jenny J. Lee; Hilary Houlette (Ali Khorsandi Taskoh, 2023)
Given the geopolitical tensions involving western nations with China and Russia, this paper investigates the extent to which China and Russia have turned toward one another, or increased their scientific collaboration. It uses bibliometric data to examine trends in China-Russia co-publications from 2013 to 2022 and the value that collaboration has had for each country's scientific output. The findings reveal that China-Russia co-publications increased markedly, and the majority of the growth occurred in multilateral co-publications. Moreover, for Russia, China has emerged as a more important international collaborator, but for China, the importance of Russia has remained relatively the same. Likewise, collaborations with China contributed more to growth in Russia's publication output compared to Russia's contribution to China's growth in output. Finally, China-Russia co-publications tended to occur in physics and astronomy and other applied science fields. These findings have implications for future collaboration between the two countries and potential challenges to the Euro-American dominance in global science.